Parapsychology : research on exceptional experiences - Henry, Jane (Routledge, 2005)
Beginning with an introduction to the methodology, this book provides the reader with a sympathetic yet critical overview of current research into unexplained phenomena including visions, telepathy, psychokinesis, and out-of-body experiences.